Integrating Indigenous Knowledge in Land Conservation: A Review of Best Practices - Sharad Bajpai; Shreya Panwar (International Journal of Land, 2025)
Indigenous knowledge systems have long played a crucial role in sustainable land conservation practices. These traditional practices, developed over centuries, offer valuable insights into ecosystem management, biodiversity preservation, and climate resilience. This review article explores best practices in integrating indigenous knowledge with modern conservation efforts, emphasizing the benefits of blending ancestral wisdom with contemporary scientific approaches.By analyzing case studies and theoretical frameworks, this study highlights successful approaches to harmonizing traditional ecological wisdom with contemporary environmental management. Various indigenous communities worldwide have implemented conservation methods such as rotational farming, controlled burns, and watershed management, which have proven effective in maintaining ecological balance. These practices align closely with global sustainability goals and provide a roadmap for enhancing conservation efforts.Additionally, this article examines the role of policy frameworks in recognizing and supporting indigenous conservation strategies. Governments and organizations must collaborate with indigenous groups to ensure their knowledge is formally included in land management policies. Conservation efforts can become more egalitarian, sustainable, and effective by incorporating indigenous perspectives into environmental governance. The findings underscore the importance of collaboration, policy inclusion, and community empowerment in achieving sustainable conservation outcomes. Successful conservation models must prioritize knowledge-sharing mechanisms, capacity-building initiatives, and legal protections for indigenous land rights. Strengthening partnerships between indigenous communities and environmental organizations can foster innovative solutions that address climate change, habitat degradation, and resource depletion. Last but not least, acknowledging and honoring indigenous knowledge systems can greatly aid in the creation of robust and flexible conservation plans.
Keywords: Community-Based Conservation; Indigenous knowledge; Land Conservation; Policy Integration; Traditional Ecological Wisdom; sustainable practices